Designing a skating robot - Lee, Bao Long. (2011)
The most important capability of humanoid robotics is that they are able to act like a human. The whole body structure of the robot is built according to a size of a human body. As the technology advances, researchers in the area field of robotics have almost the same goal in common; to make a humanoid robot that can think logically like a human and in future be able to help human with many diverse way of impossible tasks that human could not achieved. Before realizing these big dreams, every invention has to develop from the start of the basic so as to build a strong foundation. Robonova-1 is one of the most affordable humanoid robots out in the market. What makes it attractive is that it can be modified easily by simply adding modules to its control board. This project will work on how to modify Robonova-1 to a skating robot to provide entertainment purposes. It will analyze the problem encounter in both hardware and software. It was found that Robonova-1 indeed could be modified to a skating robot just by installation of two pair of rollers on its feet, however due to the sensing problem, it could not gauge accurately when gripping things it wanted to grip. Several problems were encountered with dealing the center of gravity, as Robonova-1 is balancing on it rollers instead of it pair of flat foot. Eventually all these problems were tackle in order to develop a skating robot.